(untitled) (Ukrainian Journal of Ophthalmology, 2025)
Purpose: To determine the features of corneal reparation and postoperative complications after various types of excimer laser correction (ELC) of myopia. Material and Methods: This was a multicenter, prospective, observational clinical study including 255 patients (510 eyes). They were stratified into three equal groups, based on the particular type of ELC: photorefractive keratectomy (PRK), transepithelial PRK (trans-PRK) and laser-assisted subepithelial keratectomy (LASEK). Corneal re-epithelization rate, epithelial and stromal thicknesses (as assessed by anterior segment spectral domain optical coherence tomography), corneal irregularity measurement (CIM), uncorrected visual acuity (UCVA) and incidence of haze were assessed over 3 months postoperatively. Correlation analysis and Principal Component Analysis clustering were used for assessing relationships. Results: There were statistically significant between-groups differences early after surgery. The trans-PRK group showed the best results in terms of re-epithelialization dynamics (with an incidence of delayed re-epithelialization at day 4-5 of 28% vs 38% PRK), maximum epithelial thickness in the central 5-mm map zone (64 µm vs 74 µm LASEK) and the size of stromal edema (444 µm vs 460 µm PRK). At month 3, UCVA was higher in the trans-PRK group (1.00 vs 0.90 PRK, p = 0.0059). Haze strongly correlated with stromal edema (r = 0.96, p < 0.001) and delayed re-epithelization (r = 0.93). Cluster analysis revealed subgroups with shared signs of pathological reparation irrespective of the ELC technique. The percentage of patients with a pathological cluster profile was 16.5% in the PRK group, 14.7% in the LASEK group, and 10.6% in the trans-PRK group, which confirmed independent morphometric patterns of complicated healing. Conclusion: Among the three types of ELC, trans-PRK was the best in terms of the dynamics of corneal reparation and visual recovery. Between-groups differences in morphometric and functional parameters almost disappeared at 3 months after surgery. The PRK and trans-PRK groups had the highest and lowest incidences of haze, respectively. Haze had the strongest correlations with corneal edema and delayed re-epithelialization. Cluster analysis revealed subgroups with pathological healing irrespective of the ELC technique. Morphometric parameters may be considered as predictors of complicated corneal reparation after ELC. When comprehensively assessed, they may be used for predicting the risk of complications and in further research on the new etiological factors of complicated corneal reparation.